Gastric outlet obstruction by a lost gallstone: Case report and literature review. (2017) - Koichopolos, Jennifer; Hamidi, Moska; Cecchini, Matthew; Leslie, Kenneth
Highlights: Gallstones may be lost in a laparoscopic cholecystectomy and cause morbidity. Diagnosis of complications are difficult. Findings may be mistaken for malignancies unless clinical suspicion remains high. Inflammation from lost stones can obstruct the lumen of the gastrointestinal tract. Lost gallstones are best managed during the initial cholecystectomy. Abstract: Introduction: Spilled gallstones from a laparoscopic cholecystectomy can be a source of significant morbidity, most commonly causing abscesses and fistulae. Preventative measures for loss, careful removal during the initial surgery, and good documentation of any concern for remaining intraperitoneal stones needs to be performed with the initial surgery. Case report: An 80-year-old male with a history of complicated biliary disease resulting in a cholecystectomy presented to general surgery clinic with increasing symptoms of gastric outlet obstruction. CT imaging was concerning for a malignant process despite negative biopsies. A distal gastrectomy and Billroth II reconstruction was performed and final pathology showed dense inflammation with a single calcified stone incarcerated within the gastric wall of the inflamed pylorus and no malignancy. Discussion: Stones lost during laparoscopic cholecystectomy are not innocuous and preventative measures for loss, careful removal during the initial surgery, and good documentation of any concern for remaining intraperitoneal stones. Conclusion: This is the first case of gastric outlet obstruction caused by an intramural obstruction of the pylorus from a spilled gallstone during a laparoscopic cholecystectomy and subsequent inflammation. This is an etiology that must be considered in new cases of gastric outlet obstruction and can mimic malignancy.